Inequalities in creative cities: issues, approaches, comparisons - Gerhard, Ulrike; Hölscher, Michael; Wilson, David (Palgrave Macmillan, 2017)
Introduction. Inequalities in the creative city : a new perspective on an old phenomenon / Ulrike Gerhard, Michael Hoelscher, and David Wilson -- The cultural economy of the city : pathways to theory and understanding inequality / Tom Hutton -- Urban inequality : approaches and narratives / Ferenc Gyuris -- The ideal worker : inclusion and exclusion in a knowledge-based city : the case of Oxford, UK / Linda McDowell -- Making creative cities in the global West : the new polarization and ghettoization in Cleveland, USA, and Glasgow, UK / David Wilson -- Knowledge makes cities : education and knowledge in recent urban development. The case of Heidelberg, Germany / Ulrike Gerhard and Michael Hoelscher -- "Creative urbanism" in the French south : constructing the (unequal) creative city in Montpellier / David Giband -- Entering a knowledge pearl in times of creative cities policy and strategy. The case of Groningen, Netherlands / Justin Beaumont and Zemiattin Yildiz -- Creative inequality in the mid-sized university city. Socio-spatial reflections on the Brazilian rural-urban interface : the case of Cachoeira / Wendel Henrique Baumgartner and Eberhard Rothfuss -- Regulating access and mobility of single women in a "world class" city : gender and inequality in Delhi, India / Christiana Brosius -- Conclusion / David Wilson, Ulrike Gerhard, and Michael Hoelscher
Includes bibliographical references
Keywords: Aufsatzsammlung; Kreativität; Stadt; Informationsgesellschaft; Soziale Ungleichheit; Vergleich; Stadtentwicklung; Verstädterung; Sozialwissenschaften